The Mystery Microbes - Yusoff, Durratul Fatini; Krishnan, Sivasni; Fuzhi, Fareeza Nabiela; Lokman, Nur Fazzera; Shamsaddin, Erfiana; Saad, Wan Zuhainis (UTM Academic Leadership (UTMLead), Universiti Teknologi Malaysia, 2016)
Learning is supposed to be fun. Learning happens when learners are engaged and interested. The Mystery Microbes are designed to develop interest and critical thinking of players by solving the mysteries in the game. Clues can be discovered and solved through augmented reality. The Mystery Microbes able to produce self-directed learners through this experiential and innovative learning.